DAMPAK MANAJEMEN RISIKO PADA KINERJA KEUANGAN BANK UMUM KONVENSIONAL DI INDONESIA - Hindarsih Widyastuti; Kiki Afita Andriyani; Farah Margaretha Leon (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
Abstract This study was conducted to examine the impact of risk management on the financial performance of conventional banks in Indonesia. Effective and efficient banking industry financial performance from time to time is highly expected to maintain banking financial stability itself and even the stability of a country. The increase in losses borne by banks as a result of inadequate risk management practices is a major concern of bank management and regulators. The data tested in this study is conventional bank data that listed on the Indonesia Stock Exchange during the 2015-2019 period. Data analysis using Multiple Linear Regression Model. The results show that there is a significant relationship between market risk management (NIM), operational risk management (BOPO) and liquidity risk management (LDR) with bank financial performance (ROA). Meanwhile, credit risk management (NPL) has no effect on bank financial performance (ROA). For this reason, it can be said that adequate risk management practices as demonstrated by the ratio of interest rate risk, liquidity risk and operational risk are the main driving factors for profitability for the banking sector in Indonesia. Therefore, bank management must mobilize resources to understand a sound risk management system which in turn will have an impact on improving the bank's financial performance.Keywords: Conventional Banks, Risk Management, Financial Performance.